Oksident: Yahudilik, Hıristiyanlık ve Batı aras̨tırmaları dergisi = Journal for the study on Judaism, Christianity and the West in Turkey (Muhammet Tarakci, 2019)
Oksident is a refereed and electronic journal which is published twice a year. The journal primarily includes articles on Judaism, Christianity and the West. In addition, it covers articles on the relations and polemics among Muslims, Christians and Jews. The articles that evaluate Orientalist studies on Islam and Turkey may also be published in the magazine. Articles may be written in Turkish and English.